2008
DOI: 10.1002/uog.5306
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical venous blood flow measurement: accuracy and reproducibility

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
42
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 43 publications
(93 reference statements)
9
42
1
Order By: Relevance
“…42 The ICC compares the variance of different measurements with the total variance of all measurements; with the variance derived from ANOVA using a linear mixed model in this analysis. 45 Intrasonographer and intersonographer ICC were excellent for measurement of the UCV diameter and PV, with similar or superior values to other published results. 43,44 The ICC is considered superior to Pearson's and Spearman's analyses as it takes into account the differences between observers 42 and the variance of all measurements.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…42 The ICC compares the variance of different measurements with the total variance of all measurements; with the variance derived from ANOVA using a linear mixed model in this analysis. 45 Intrasonographer and intersonographer ICC were excellent for measurement of the UCV diameter and PV, with similar or superior values to other published results. 43,44 The ICC is considered superior to Pearson's and Spearman's analyses as it takes into account the differences between observers 42 and the variance of all measurements.…”
Section: Discussionsupporting
confidence: 84%
“…The ICC value can range from 0 to 1, with a value greater than 0.8 indicating almost perfect agreement. 25,44,45 Published data indicated that the largest umbilical vein diameter occurs during the third trimester, somewhere between 32 and 42 weeks GA. 45 Intrasonographer and intersonographer ICC were excellent for measurement of the UCV diameter and PV, with similar or superior values to other published results.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal echocardiography-derived Doppler flow measures such as pulsatility index calculations are a measure of vascular resistance, not flow. Doppler-derived volumetric calculations of umbilical venous flow as an absolute measure of placental blood flow, or perhaps as a relative fraction of overall fetal combined cardiac output may be more informative [30]. Other methodologies such as MRI techniques will add to the capacity to better gauge the relationship between blood flow and placental structure and function during pregnancy, which will complement fetal echocardiography and add important insights to our understanding [10, 31].…”
Section: Discussionmentioning
confidence: 99%
“…[11-14]) or 3D power Doppler measurements of the placental blood flow (e.g. [15-19]), and have noted the effect that different placental attachments in utero have on the transport efficiency.…”
Section: Discussionmentioning
confidence: 99%